2022
DOI: 10.2106/jbjs.21.01159
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Reporting Race, Ethnicity, and Socioeconomic Status in Studies Published in Top Orthopaedic Journals

Abstract: Background:Although there have been calls for the routine reporting of patient demographics associated with health disparities, including race, ethnicity, and socioeconomic status (SES), in published research, the extent to which these variables are reported in orthopaedic journals remains unclear.Methods:We identified and examined all research articles with human cohorts published in 2019 in the 2 highest-ranked U.S. general orthopaedics journals, Clinical Orthopaedics and Related Research and The Journal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Several studies have shown that SDOH, including sex, race, ethnicity, education level, and income, are independent predictors of surgical management and outcomes. [5][6][7][8] Many of the studies included in this scoping review used postoperative complications, such as incidence of cerebrospinal fluid leaks and diabetes insipidus, and hospitalization metrics, such as readmission rates, as the primary outcome measures (►Supplementary Table S1, available in the online version). Goljo et al found that the likelihood of postoperative complications was higher in Black and Hispanic patients compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that SDOH, including sex, race, ethnicity, education level, and income, are independent predictors of surgical management and outcomes. [5][6][7][8] Many of the studies included in this scoping review used postoperative complications, such as incidence of cerebrospinal fluid leaks and diabetes insipidus, and hospitalization metrics, such as readmission rates, as the primary outcome measures (►Supplementary Table S1, available in the online version). Goljo et al found that the likelihood of postoperative complications was higher in Black and Hispanic patients compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
“…5 Studies in ophthalmology and orthopedics reviewed their field's literature from top journals over a 1-year period and also found that sociodemographics were routinely underreported. 6,7 Studies evaluating reporting of sociodemographics has not been performed in the pituitary surgery literature. Research has demonstrated disparities in complication rates in pituitary surgery based on race, ethnicity, socioeconomic status (SES), insurance status, and hospital factors.…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 40 , 44 , 45 , 64 However, the rate of reporting of these metrics is low in top orthopaedic journals. 22 Within foot and ankle orthopaedics, one previous systematic review organized SES and race reporting for RCTs encompassing all foot and ankle surgery. 64 Although this review found evidence demonstrating consistent underreporting of SEC and race within foot and ankle surgery, it was limited to only a 6-year time frame (2016-2021) and only described studies within 4 specific journals.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, studies also have shown that these variables have been drastically under-reported in randomized controlled trials (RCTs) across many medical and surgical specialties, 6 , 7 , 8 including orthopaedic RCTs. 9 , 10 , 11 …”
mentioning
confidence: 99%